PENGGUNAAN POTRET UNTUK PROMOSI PRODUK DALAM PERSPEKTIF HAK KEKAYAAN INTELEKTUAL - NIM. A1011181144, FRANSISKA KURNIAWATI (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractIn this modern era, it is often found that portraits are used for product promotion in order to gain economic value without obtaining permission from the owner of the portrait. Portrait are copyright works, Intellectual property rights are protected under The Law Number 28 of 2014 Concerning Copyrights. One of which is the copyright of works of art of expression namely Portraits. So, this research was conducted to discuss how the implementation of the use of portraits for promotion and how portraits are used without permission from the poiny of view of business ethics.The research used here is